2010
DOI: 10.1515/humr.2010.021
|View full text |Cite
|
Sign up to set email alerts
|

Humor in intimate relationships: Ties among sense of humor, similarity in humor and relationship quality

Abstract: The present study examined relations between different aspects of humor and relationship quality. Participants, 114 married or cohabiting heterosexual couples from the general community, with a mean relationship length of 22 years, completed a number of measures assessing these two themes. We expected different aspects of humor of both partners to be positively related to relationship quality. In addition, we expected partners to resemble each other with regard to the different aspects of humor, and similarity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 50 publications
2
32
0
1
Order By: Relevance
“…Taking just a few examples, Edwards and Martin19 reported that the ability to produce humor (add witty captions to cartoons) did not predict who would score higher on well-being measures, whereas sense of humor scores did. On the other hand, sense of humor did not predict relationship quality, but ability to produce humor did, at least for women 20. A personal liking for humor, a subscale of Thorson and Powell’s Multidimensional Sense of Humor Scale, has been negatively associated with wellbeing.…”
Section: Introductionmentioning
confidence: 87%
“…Taking just a few examples, Edwards and Martin19 reported that the ability to produce humor (add witty captions to cartoons) did not predict who would score higher on well-being measures, whereas sense of humor scores did. On the other hand, sense of humor did not predict relationship quality, but ability to produce humor did, at least for women 20. A personal liking for humor, a subscale of Thorson and Powell’s Multidimensional Sense of Humor Scale, has been negatively associated with wellbeing.…”
Section: Introductionmentioning
confidence: 87%
“…Beyond initial attraction, sharing humourous experiences and laughing together also increases feelings of closeness ( Fraley & Aron, 2004 ). More specifically, romantic partners who share similarities in what they find to be humourous tend to see their partners in a more favourable light and have greater optimism for the future of their relationship ( Barelds & Barelds-Dijkstra, 2010 ; Murstein & Brust, 1985 ). This may be the case because similarities in humour may be representative of similarities in personal values, needs, and preferred methods of communication, factors that have been demonstrated as important in mate selection (e.g., Abel, 2002 ; Driver & Gottman, 2004 ; Kelly, 2002 ).…”
mentioning
confidence: 99%
“…Through bonding, workers realize a common set of values that can be beneficial to the firm and its output. Absenteeism and shirking can be avoided as a workforce is cemented together (Barelds and Barelds-Dijkstra, 2010) That is, the "bonding aspect of humor may have a significant impact on workplace productivity and employee levels of satisfaction" (Vinton, 1989). Workers who can socialize effectively in the workplace are less likely to avoid it.…”
Section: Humor As Communicationmentioning
confidence: 99%